Business sustainability practice (BSP) profile assessment in Malaysia economic sectors using K-mean clustering approach - Nur Soliha, Sahimi (2020)
In recent years, our planet faces massive social, environment and economical challenges. Meanwhile, only 40% of the companies registered in Bursa Malaysia embed a sustainability concept in their whole projects or businesses due to lack of participation and awareness on sustainability as reported in the Environmental Democracy Index (EDI), Sustainable Developement Index (SDI) and Human Developement Index (HDI). Therefore, no competitive edge among Malaysia Economic Sectors has been achieved. In Malaysia, there were only several academic studies or business reports presenting how a few companies that incorporate sustainability in their businesses nature. In order to combat these issue and achieve a better sustainability practices, an integration technique of the Business Sustainability Practice (BSP) was proposed to assess the BSP performance by using the K-Mean clustering approach and result validation using the Expert Elicitation method. From this attempts, the gap between the practice elements of knowledge and consciousness is improved through proper guidance, and this technique is acknowledged by the experts. From this research there are two main results which are the development of an integrated BSP which associate the perceptional (attitudinal) and knowledge through mapping between Sustainability Development Goals (SDG) and Green Project Management (GPM); secondly, the clustering and sector profiling on sustainability practice shown steadfast in consciousness but limited in knowledge of sustainability. Most of the clusters were located at the first and second quadrant. Then the best BSP performance is mining and quarrying’s sector which at steady state in sustainable practice with fully incorporated at planet’s attribution which are transport, energy, water, waste, and material and procurement. In contrast, the agriculture shows volatile trend for every attribution rather than other economic sectors. The collective feedback was agreed with the integrated system for Business Sustainability Practice (BSP) as found in the first finding as the solution for the Malaysian economic performance and the BSP profile for the second finding, where 100% of feedback agreed with both research findings to be implement later on. The feedback from the expert is this research finding is one of the good imitative thus will use in wider application to promote the competitive edge among Malaysia economic sectors in Malaysia. Now, it is time for every business in every sector and industry in Malaysia to take a serious action that will improve awareness and enhance Malaysia’s index rank to be among developed countries in the future.